(untitled) (American Journal of Islam and Society, 1989)
A seminar was organized by the International Institute of Islamic Thought, on Dhu al Hijjah 15-16, 1409/July 18-19, 1989, at Zamalek, Cairo, to discuss the indexing of the Holy Qur’an. In the first session, research papers and repom by members of the seminar were presented. In the second and third sessions, the papers were discussed from different angles. During the closing session, the recommendations prepared by the drafting committee were discussed. First: Project Objectives The International Institute of Islamic Thought took the responsibility for the task of the Islamization of knowledge. The natural approach would be to make the two main sources of Islamic knowledge-the Qur’an and the Sunnah-accessible to research scholars in the humanities and social sciences. This project aims - during this stage-at analyzing the contents of the Qur‘anic verses to classify them according to the different branches of knowledge, and to arrange them under suitable headings, in order to make it easy for research scholars to find the verses they want in the fields of the humanities and social sciences. Second: Indices and Concordances Participants in the seminar exchanged consultations regarding whether it is suitable to compile a list of topics (index) first, then proceed with the classification process accordingly, or should the classification be completed first on the basis of topics to be found, followed by the cornpilafion of an index. After completing the discussion, it was decided to follow both approaches simultaneously as indicated below: ...